Compensation, working environment, and employee performance: A study in one of the municipal water supply companies in West Java - Aribowo, Agus; Nurbasari, Anny; Karamang, Ezra (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2023)
Along with the increasingly advanced era, human resources are vital for small and large companies because their position drives all activities to achieve their goals. Similarly, the municipal water supply company also needs employees to serve society well. Therefore, some roles, like compensation and working environment, are necessary to attain this situation. Based on this circumstance, this study examines their impact on employee performance. Moreover, to reach this purpose, this study distributes the questionnaire to the 113 municipal water supply employees in one of the West Java regencies as the samples, taken by simple random sampling technique. Also, a survey is employed to collect data. The regression model and t-statistic are utilized to analyze the data and examine the proposed hypotheses. In conclusion, this study declares that their performance is positively affected by the work environment. Conversely, it is not influenced by compensation.